A rare case of live full-term fetus in primary abdominal pregnancy - Chandrayan, Piyusha; Patel, Arpana (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
This is a case report presenting, gravida 3 para 2 live 1 with primary abdominal pregnancy. It is a potentially life-threatening form of ectopic gestation with an incidence of 1% of all the ectopic pregnancies. In this case, the patient delivered a full-term male baby. The baby cried immediately after birth. The patient was stable post operatively but on 10th POD, developed pancytopenia with pleural effusion. The pancytopenia was methotrexaate induced. She was admitted in ICU and was given oxygenation, folinic acid and higher antibiotics. She was discharged on 20th POD after vitally and hemodynamic stability. In this case, though the patient was managed effectively but abdominal pregnancy is associated with significant maternal morbidity and mortality. Therefore, early diagnosis of the case still remains the most important modality for efficient management of the patient.